2007
DOI: 10.1211/jpp.59.11.0004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of calcium salt solubility with changes in pH and PCO2, simulating varying gastrointestinal environments

Abstract: The amount of calcium available for absorption is dependent, in part, on its sustained solubility in the gastrointestinal (GI) tract. Many calcium salts, which are the calcium sources in supplements and food, have pH-dependent solubility and may have limited availability in the small intestine, the major site of absorption. The equilibrium solubility of four calcium salts (calcium oxalate hydrate, calcium citrate tetrahydrate, calcium phosphate, calcium glycerophosphate) were determined at controlled pH values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 20 publications
(20 reference statements)
2
95
0
2
Order By: Relevance
“…In the present study, famotidine aggravated the condition of the patients by augmenting hypocalcaemia state after 4 mo. This effect is supported by Goss et al, 2007 who explained that at neutral pH, calcium carbonate is practically insoluble in water, but although the solubility of calcium salts may be highly pH dependent, calcium absorption is unaffected by alterations in gastric acid secretion [20] In this study, it has also been found that famotidine with caco . 3 did not show any significant change in serum PTH, which contradicted by the study of Bricker, who suggested that original proposal was that phosphate retention as a result of reductions in glomerular filtration rate would cause transient decreases in the levels of calcium, which would, in turn, trigger an increase in PTH secretion and a new steady state would be achieved, with restoration of normal calcium and phosphate levels but, with the consequence that high levels of PTH now would be required to maintain homeostasis [21] The present study shows a significant decrease in serum ALP level upon administration of famotidine in combination with caco .…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, famotidine aggravated the condition of the patients by augmenting hypocalcaemia state after 4 mo. This effect is supported by Goss et al, 2007 who explained that at neutral pH, calcium carbonate is practically insoluble in water, but although the solubility of calcium salts may be highly pH dependent, calcium absorption is unaffected by alterations in gastric acid secretion [20] In this study, it has also been found that famotidine with caco . 3 did not show any significant change in serum PTH, which contradicted by the study of Bricker, who suggested that original proposal was that phosphate retention as a result of reductions in glomerular filtration rate would cause transient decreases in the levels of calcium, which would, in turn, trigger an increase in PTH secretion and a new steady state would be achieved, with restoration of normal calcium and phosphate levels but, with the consequence that high levels of PTH now would be required to maintain homeostasis [21] The present study shows a significant decrease in serum ALP level upon administration of famotidine in combination with caco .…”
Section: Discussionsupporting
confidence: 66%
“…Unlike the well-buffered apical solution in a Ussing chamber (i.e., the estimated PTH-induced HCO 3 Ϫ flux of ϳ135 pmol·s Ϫ1 ·cm Ϫ2 was not large enough to shift the [HCO 3 Ϫ ]-to-PCO 2 ratio of the buffer solution), the unbuffered ileal fluid would have been alkalinized by the robust HCO 3 Ϫ secretion. Since the ileum is the principal site for phosphate absorption (45), this PTH action could be of physiological significance because phosphate should precipitate as nonabsorbable complexes in the ileal alkaline lumen (11,24), thus fulfilling the classical hypophosphatemic action of PTH (54). On the other hand, in lower vertebrates, the PTH function with regard to HCO 3 Ϫ secretion and the responsive gastrointestinal segment may differ from that in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium absorption occurs primarily in the duodenum where gastric acid secretion permits to obtain a pH o6.0 necessary for the solubilization of calcium salts from ingested food (Goss et al, 2007). Gastric acid production is not only stimulated by the parasympathetic nervous system but also by chemical signals, nutrients, including Ca 2 þ (Hade and Spiro, 1992;Geibel and Wagner, 2006) and some amino acids (Konturek et al, 1978;Strunz et al, 1978).…”
Section: Modulations Of Intestinal Dietary Calcium Absorptionmentioning
confidence: 99%